Methodologies for studying depression in persons living with tuberculosis: Protocol for a scoping review. - Amanda J Gupta; Patricia Turimumahoro; Lori Rosman; Jonathan E Golub; David W Dowdy (PLoS ONE)
Tuberculosis (TB) and depression frequently co-occur, yet research has largely focused on prevalence rather than diagnostic or treatment methodologies. Given overlapping symptoms, robust research approaches are critical for improving detection and treatment strategies in persons with TB (PWTB). This protocol defines a scoping review that aims to map methodologies used to study depression in individuals with TB, identifying gaps in research design, diagnosis, and treatment that may hinder clinical and public health advancements. A search was conducted in MEDLINE, Embase, PsycINFO, Global Health, Cochrane Library, and Africa-Wide Information using controlled vocabulary related to TB and depression. Studies examining the TB-depression relationship will be included. We will use Covidence to facilitate screening, selection, and data extraction. We will extract data on study design, diagnostic tools, treatment interventions, and analytical approaches. Descriptive characteristics of included studies will be presented using figures and tables. Using the Reach-Effectiveness-Adoption-Implementation-Maintenance (RE-AIM) framework, we will evaluate reach by assessing the extent to which studies explore both directions of the TB-depression relationship and include diverse, high-risk populations. Effectiveness will be examined by categorizing study designs to assess methodological diversity and evaluating the diagnostic tools and treatment interventions used, along with their reported efficacy. Adoption will be analyzed by identifying where and by whom depression diagnosis and treatment methodologies have been implemented and whether research findings have influenced clinical guidelines or public health policies. Implementation will be assessed by identifying barriers and facilitators reported in qualitative studies or by researchers regarding the integration of depression care into TB treatment settings. Finally, maintenance will be determined by examining whether diagnostic and treatment methodologies were sustained within health systems, including long-term patient outcomes and the persistence of interventions beyond the research phase. By mapping existing methodologies and identifying research gaps, this review will provide valuable insights to guide future research study designs and improve diagnostic and treatment strategies for depression in PWTB.